Emerging field: O-GlcNAcylation in ferroptosis - Zhang, Hongshuo; Zhang, Juan; Dong, Haojie; Kong, Ying; Guan, Youfei (Frontiers in Molecular Biosciences, 2023)
In 2012, researchers proposed a non-apoptotic, iron-dependent form of cell death caused by lipid peroxidation called ferroptosis. During the past decade, a comprehensive understanding of ferroptosis has emerged. Ferroptosis is closely associated with the tumor microenvironment, cancer, immunity, aging, and tissue damage. Its mechanism is precisely regulated at the epigenetic, transcriptional, and post-translational levels. O-GlcNAc modification (O-GlcNAcylation) is one of the post-translational modifications of proteins. Cells can modulate cell survival in response to stress stimuli, including apoptosis, necrosis, and autophagy, through adaptive regulation by O-GlcNAcylation. However, the function and mechanism of these modifications in regulating ferroptosis are only beginning to be understood. Here, we review the relevant literature within the last 5 years and present the current understanding of the regulatory function of O-GlcNAcylation in ferroptosis and the potential mechanisms that may be involved, including antioxidant defense system-controlled reactive oxygen species biology, iron metabolism, and membrane lipid peroxidation metabolism. In addition to these three areas of ferroptosis research, we examine how changes in the morphology and function of subcellular organelles (e.g., mitochondria and endoplasmic reticulum) involved in O-GlcNAcylation may trigger and amplify ferroptosis. We have dissected the role of O-GlcNAcylation in regulating ferroptosis and hope that our introduction will provide a general framework for those interested in this field.